Antitumor effects of Chinese herbal medicine compounds and their nano-formulations on regulating the immune system microenvironment - Sun, Kexiang; Wu, Linguangjin; Wang, Shuyun; Deng, Wanli (Frontiers in Oncology, 2022)
Traditional Chinese medicine (TCM), including herbal medicine, acupuncture and meditation, has a wide range of applications in China. In recent years, herbal compounding and active ingredients have been used to control tumor growth, reduce suffering, improve quality of life, and prolong the life span of cancer patients. To reduce side effects, herbal medicine can be used in conjunction with radiotherapy and chemotherapy or can be used as an adjuvant to strengthen the immune effect of anticancer vaccines. In particular, in the immunosuppressed tumor microenvironment, herbal medicine can have antitumor effects by stimulating the immune response. This paper reviews the advances in research on antitumor immunomodulation in Chinese herbal medicine, including the regulation of the innate immune system, which includes macrophages, MDSCs, and natural killer cells, and the adaptive immune system, which includes CD4+ T cells, CD8+ T cells, and regulatory T cells (Tregs), to influence tumor-associated inflammation. In addition, a combination of active ingredients of herbal medicine and modern nanotechnology alter the tumor immune microenvironment. In recent years, immunological antitumor therapy in TCM has been applied on a reasonably large scale both nationally and internationally, and there is potential for further clinical expansion. Investigation of immune modulation mechanisms in Chinese herbal medicine will provide novel perspectives of how herbal medicine controls tumor growth and metastasis, which will contribute to the evolution of tumor research. Methodology Experimental research between the years of 2012-2022, meta-analysis and reviews for the period 2002-2022 found on the Databases including PubMed, Embase, and the Cochrane database were used. The inclusion criteria were experimental research literature addressing the anti-tumor immunological effects of active ingredients and nanoparticles in Chinese herbal medicine. Exclusion criteria were articles that addressed Chinese herbal medicine and nano-formulations without discussing anti-tumor immunological effects in innate, adaptive immune cells, MDSCs, and nuclear factors.